Assessing Ferrous Level in Neonates Suffering from Hypoxic Ischemic Encephalopathy - Asifa Ashraf, Muhammad Shoaib, Sana Sabir, Naghmana Lateef, Ambreen Tauseef, Tanzeela Akram, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the ferrous level in Hypoxic Ischemic Encephalopathy. Methodology: Eighty four neonates from tertiary care hospital had been included. Neonates were classified as hypoxic on the basis of Sarnat and Sarnat scoring. 34 healthy neonates served as control. Among 50 patients two groups were made each containing 25 neonates. Group 1 comprising of 25 neonates of hypoxic ischemic encephalopathy of mild degree. Group 2 comprising of 25 neonates suffering from moderate to severe encephalopathy. Results: Serum ferrous was significantly elevated in neonates suffering from Hypoxic Ischemic Encephalopathy. Conclusion: The significant elevation of serum ferrous in hypoxic neonates reiterates the key role of serum ferrous in neonates with hypoxic ischemic encephalopathy.